Analisis Pendapatan Usaha Ternak Sapi Perah Di Kecamatan Cepogo Kabupaten Boyolali - E. T. Rahayu (Universitas Sebelas Maret (UNS), 2013)
The research purposed to know the income analysis of dairy farm and the influence of use theproduction factors in Cepogo Boyolali Central Java. The research was conducted from August to October 2011.Survey method was used for this research using purposive sampling to choose the respondent for sample unit. Samples were taken from 60 respondents rearing at least 1 lactating Friesian Holstein Crossbreed dairy cattle. The variables observed were the concentrate cost (X1), grass cost (X2), medicine cost (X3), labor cost (X4), and purchase cost of dairy cattle (X5). Data were calculated to know the income and analysed with multiple linear regression. The results showed that the equation of regression analysis is Y = -4.553 + 0.048 X1 + 0.428 X2 + 0.075 X3 + 0.567 X4 + 0.679 X5 with R2 = 0.775, which means that 77.5% of independent variables affect the model while the rest are influenced by outside variables studied. Based on the results of the F test , the cost of concentrate feed ( X1 ), the cost of green feed ( X2 ) , drug costs ( X3 ), labor costs ( X4 ) and the cost of purchasing dairy cows ( X5 ) jointly affect revenues dairy cattle, whereas the t test only the cost of purchasing the most influential dairy cows. Average of farmersincome for one year is Rp. 7,803,395.833. It means dairy cattle business can be maintained at the study site as a source of income of farmers. The conclusion of this study is the people's dairy business in District of Cepogo still profitable with an average scale ownership 3 lactating cows. The cost of purchase of dairy cows is the most influential factor production in farm dairy cattle.Key words: Income Analysis, Production Factors, Dairy Farm